Dynamics of Development of Dadaman Coffee Production as One of the Livelihoods of the Sibopong Community - Lestari, Ria Yuni; Eliza, Nova; Satibi, Febrianti; Hanop, Hanop; Diharja, Dias Ramadhan; Oktapiani, Eka Ripa; Nurjanah, Sri; Abdillah, Zaqi Muhammad; Hadifatuzzahra, Fadia; Fajri, Fajri (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This research aims to analyze the dynamics of the development of Dadaman coffee production in Sibopong Village as one of the livelihoods of the local community. The analytical method applied involves field surveys, in-depth interviews with farmers, and collecting historical data on Dadaman Coffee production. The research results reveal significant changes in Dadaman coffee production over the last few years, which are influenced by factors such as climate conditions, the application of agricultural techniques, and the dynamics of market demand. In this approach, research provides an in-depth understanding of the challenges and opportunities faced by Dadaman coffee farmers. It was found that climate change is having a marked impact on crop yields, while the adoption of innovative farming techniques could be the key to increasing production. This research provides a comprehensive understanding of local realities in Sibopong Village, which aims to develop sustainable agricultural strategies and economic policies that support community welfare, so that it can become a valuable reference for stakeholders, researchers and policy makers.